2010
DOI: 10.1074/jbc.m109.093799
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-3 Is Increased and Participates in Neuronal Apoptotic Signaling Downstream of Caspase-12 during Endoplasmic Reticulum Stress

Abstract: Although endoplasmic reticulum (ER) stress-induced apoptosis has been associated with pathogenesis of neurodegenerative diseases, the cellular components involved have not been well delineated. The present study shows that matrix metalloproteinase (MMP)-3 plays a role in the ER stress-induced apoptosis. ER stress induced by brefeldin A (BFA) or tunicamycin (TM) increases gene expression of MMP-3, selectively among various MMP subtypes, and the active form of MMP-3 (actMMP-3) in the brain-derived CATH.a cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 43 publications
0
62
0
Order By: Relevance
“…Related to Parkinsonism, in vitro studies have demonstrated intracellular activation of MMP-3 after neuronal stress, with consequent induction of apoptotic-signaling cascades Kim et al 2010). MMP-3 released by dying neurons activates microglia, further contributing to neurodegeneration (Kim et al 2007) along with MMP-9 (Woo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Related to Parkinsonism, in vitro studies have demonstrated intracellular activation of MMP-3 after neuronal stress, with consequent induction of apoptotic-signaling cascades Kim et al 2010). MMP-3 released by dying neurons activates microglia, further contributing to neurodegeneration (Kim et al 2007) along with MMP-9 (Woo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A high level of extracellular actMMP-1 and/or actMMP-3 might not only dissolve the extracellular matrix leading to CCh but also contribute to anoikis, which is a form of apoptosis because of interruption of cell-matrix adhesion. 41 Nonetheless, we could not ignore the role of intracellular actMMP-1 and actMMP-3, which have also been implicated to lead to cell death of cultured neurons and myocyte cells, 42,43 as well as cell DArgic neurons and hepatic myofibroblasts, 21,23,44 respectively. Because Aprotinin (an inhibitor of serine proteinase that is known to activate MMPs) 45 achieved the same extent of rescue as Batimastat (a competitive, reversible, and broad-spectrum inhibitor of MMPs, especially MMP-1) 46 and NNGH (an MMP-3-specific inhibitor), 23,24 we suspect that the action of PTX3 in controlling activation of MMP-1 and MMP-3 might reside not only at the transcriptional and translational levels but also post translational activation of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Batimastat, an inhibitor of both MMP1 and MMP3, and centrifugal filter units were purchased from EMD Millipore (Billerica, MA). N-isobutyl-N-(4-methoxyphenylsulfonyl)-glycylhydroxamic acid (NNGH), a specific MMP-3 inhibitor, [22][23][24] was purchased from Enzo Life Sciences, Inc. (Farmingdale, NY). DeadEnd Fluorometric TUNEL System and RQ1 RNase-Free DNase were purchased from Promega (Madison, WI).…”
mentioning
confidence: 99%
“…In addition, MMP-3 produced by the activated microglia can be released into the extracellular matrix, further exacerbating the neuroinflammatory process [324]. In contrast, overexpression of TIMP-1 results in the attenuation of apoptosis in neuronal cells, along with the suppression of MMP-3 activity [325]. TIMP-1 is also neuroprotective, both against excitotoxic neuronal death [326] and against traumatic and ischemic brain injury in mice [327].…”
Section: Metalloproteinases and Neurodegenerative Diseasesmentioning
confidence: 99%